Masticatory muscle activity evaluation by electromyography in removable partial denture users - Amorim, José Benedito Oliveira; Rabelo, Sylvia Bicalho; Souza, Ana Carolina; Corazza, Pedro Henrique; de Araújo, Rodrigo Máximo; Cavalcanti, Sâmia Carolina Mota; Valera, Márcia Carneiro (Brazilian Dental Science, 2013)
Objectives: The aim of this study was to evaluateby electromyography the activity of the temporalisand masseter muscles in removable partial dentures(RPDs) users, before and after new RPDs installation.Material and Methods: Ten patients were selectedfor this study. All subjects were edentulous in theposterior mandibular region (Kennedy class I orII), fully dentate in the antagonist arch, and dentalprosthesis users, which needed to be replaced. Theelectromyographic activity (EMG) recorded thesuperficial masseter and temporalis muscles, duringthe maximum voluntary bite force and the restposition. Maximum mouth opening was also verified.The measurements were recorded at four specifictimes: using the old prosthesis (T0), right after thenew prosthesis installation (T1), two weeks (T2) andfour weeks (T4) after installing the new prosthesis.All the RPDs were made by an experienced dentistand the same laboratory. Data were statisticallyanalyzed by ANOVA and Tukey tests (? = 0.05).Results: EMG values had high standard deviation atthe time T0. Generally, the mean values decreasedafter new prosthesis installation, especially aftertwo weeks from the installation (T2). During therest position, the left masseter and left temporalismuscles showed statistically significant gradualdecrease in their activities over time. Conclusion:New prostheses have positive effect on the patient’smuscular activity. However, an adaptation period ofthe muscle fibers to the new prosthesis is needed.KeywordsElectromyographic activity; Dental occlusion; Masseter; Removable partial dentures; Temporalis.